1994
DOI: 10.1136/jnnp.57.12.1525
|View full text |Cite
|
Sign up to set email alerts
|

Chronic idiopathic axonal polyneuropathy: a five year follow up.

Abstract: Seventy five patients with chronic idiopathic axonal polyneuropathy (CLAP) were studied for five years. The standardised and quantified neurological examination shows that progression of CIAP is slow, and handicap, if present, is not severe. During the follow up period a definite cause of the neuropathy was found in only four patients (two hereditary motor and sensory neuropathy type 2, one sensory chronic inflammatory demyelinating polyneuropathy, one alcoholic neuropathy). At the end of the follow up CLAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 9 publications
4
82
0
Order By: Relevance
“…Such a comprehensive investigation yields an etiologic diagnosis in 74 to 82% of patients with polyneuropathy. [4][5][6][7][8][9][10][11][12][13] Laboratory test results must be interpreted in the context of other clinical information since the etiologic yield of laboratory testing alone is limited by the low specificity of many of the tests. For example, one study of idiopathic polyneuropathy found that laboratory tests alone had only a 37% diagnostic yield (Class III).…”
Section: Analysis Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Such a comprehensive investigation yields an etiologic diagnosis in 74 to 82% of patients with polyneuropathy. [4][5][6][7][8][9][10][11][12][13] Laboratory test results must be interpreted in the context of other clinical information since the etiologic yield of laboratory testing alone is limited by the low specificity of many of the tests. For example, one study of idiopathic polyneuropathy found that laboratory tests alone had only a 37% diagnostic yield (Class III).…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…10 The majority of studies indicated that screening laboratory tests comprised of a complete blood count, erythrocyte sedimentation rate, comprehensive metabolic panel (blood glucose, renal function, liver function), thyroid function tests, serum B12, and serum protein immunofixation electrophoresis are indicated for most patients with polyneuropathy. [4][5][6][7][8][9][10][11][12][13] Five Class III studies indicated that the highest yield of abnormality was seen with screening for blood glucose, serum B12, and serum protein immunofixation electrophoresis. 4,6,10,13,14 The test with the highest yield was the blood glucose, consistent with the well-known fact that diabetes mellitus is the most common cause of DSP.…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…RESULTS Included cases. We identified 93 randomly selected genetically unresolved cases from our Neuropathy DNA Sample bank, including the following: hereditary motor and sensory polyneuropathy (HMSN) type 2 (HMSN2; n 5 80); HMSN1 (n 5 1); HMSN unclassified (n 5 3); chronic idiopathic axonal polyneuropathy (n 5 6), defined as polyneuropathy with distal leg sensory predominant symptoms, without family history 21,22 ; and hereditary motor neuropathy (n 5 3). The mean age at the initial evaluation was 54 years (range 2-86), and the mean age at polyneuropathy onset was 41 years (range 2-85).…”
mentioning
confidence: 99%
“…CIAP has a slowly progressive course, and during a 5-year follow-up no cause was found. 22,23 Clinical data of patients are listed in table 1. Biopsy findings were not used to assign diagnoses except in cases of vasculitis, for which well-established morphological criteria exist.…”
mentioning
confidence: 99%